Keterampilan Membaca Komprehensif Pelajar Sekolah Dasar - Fadlilah, Megah Endah; Adiwijaya, Satria Nugraha (PAKAR Pendidikan, 2024)
Changes in a learner's reading phase have implications for other aspects of language skills. Moreover, changes in students' reading demand higher output. This research aims to determine the comprehensive reading skills of elementary school students transitioning from lower grades to higher grades. The type of research used is qualitative research using a descriptive approach. The population in this study was 24 students of class IV science at Muhammadiyah Ibtidaiyah Madrasah Hadimulyo Metro City. The tea sampling technique is nonprobability sampling type purpose sampling with data collection methods through tests and interviews. Based on the results of the research data analysis that has been carried out, it can be concluded that comprehensive reading skills in the assessment criteria could be better, with an average score of 64.2. From this score, students are not proficient in comprehensive reading skills because they have yet to be able to reach the Criteria Score. Minimum completeness determined is 75. The result shows that students need help with comprehensive reading skills in class IV science. This research provides the view that there is a change in the concept of acquiring reading content based on comprehensive reading aspect, namely reading speed, understanding simple meanings, significant meaning understanding, evaluation assessment of content and form, and reading speed flexible and based on the type of reading skill students use.